2009
DOI: 10.2967/jnumed.109.063529
|View full text |Cite
|
Sign up to set email alerts
|

A Multitracer Dopaminergic PET Study of Young-Onset Parkinsonian Patients With and Without Parkin Gene Mutations

Abstract: The impact of parkin gene mutations on nigrostriatal dopaminergic degeneration is not well established. The purpose of this study was to characterize by PET using 18 F-fluoro-L-3,4-dihydroxyphenylalanine ( 18 F-fluoro-L-DOPA), 11 C-PE2I, and 11 C-raclopride the pattern of dopaminergic lesions in young-onset Parkinson disease (YOPD) patients with or without mutations of the parkin gene and to correlate the clinical and neuropsychologic characteristics of these patients with PET results. Methods: A total of 35 Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 36 publications
5
17
1
Order By: Relevance
“…[9][10][11] Changes in extrastriatal [ 11 C]raclopride binding have also been associated with brain pathologies such as Parkinson's, Huntington's, and Alzheimer's diseases. [12][13][14] The loci of the extrastriatal reductions of [ 11 C]raclopride binding in the abovementioned studies are also consistent with the distribution of extrastriatal D 2/3 receptors reported in postmortem studies, where the thalamus has the highest density of D 2/3 receptors followed by the lateral temporal cortex, the anterior cingulate, and the frontal cortex. 15 The region of interest (ROI) measurement of striatal D 2/3 receptor binding using single-bolus [ 11 C]raclopride injection is highly reliable.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…[9][10][11] Changes in extrastriatal [ 11 C]raclopride binding have also been associated with brain pathologies such as Parkinson's, Huntington's, and Alzheimer's diseases. [12][13][14] The loci of the extrastriatal reductions of [ 11 C]raclopride binding in the abovementioned studies are also consistent with the distribution of extrastriatal D 2/3 receptors reported in postmortem studies, where the thalamus has the highest density of D 2/3 receptors followed by the lateral temporal cortex, the anterior cingulate, and the frontal cortex. 15 The region of interest (ROI) measurement of striatal D 2/3 receptor binding using single-bolus [ 11 C]raclopride injection is highly reliable.…”
supporting
confidence: 88%
“…[9][10][11] Changes in extrastriatal [ 11 C]raclopride binding have also been associated with brain pathologic assesment, such as Parkinson's, Huntington's, and Alzheimer's diseases. [12][13][14] Moreover, a recent study using diffusion-weighted magnetic resonance imaging and PET found that connectivity-based subdivision of human striatum improved the evaluation of regional differences in DA transmission, supporting an association between striatal DA release and cortical connectivity. 35 36,37 In the current study, cortical VAR and ICC values were good to moderate, ranging from 6.1%, 0.79 (temporal cortex) to 13.1%, 0.67 (superior frontal gyrus).…”
Section: Discussionmentioning
confidence: 89%
“…Since it is commonly accepted that motor symptoms appear earliest after 50% and more of nigrostriatal neurons are lost, PET techniques obviously are sensitive enough to pick up that loss at an earlier stage [40] . This is further supported by pathologic PET findings in asymptomatic subjects of examinations in twins, familial PD, parkin and other inherited PD kindreds [33,[41][42][43][44] .…”
Section: Pet Imaging Of Presynaptic Dopaminergic Functionssupporting
confidence: 53%
“…PET imaging of presynaptic terminal functions, therefore, reveals reduced radioligand uptake in the striatum of PD patients with a more pronounced decrease in the (posterior) putamen than in the caudate, and usually shows an asymmetry with more severe affection of the striatum contralateral to the clinically more affected limbs [8][9][10][30][31][32] . This pattern has not only been reported in sporadic PD but also in juvenile, young-onset parkinsonism and patients with parkin gene mutations [33][34][35] . Generally, significant correlations between disease severity and disability stages with the extent of the reduction in presynaptic terminal measures have been reported [15,31,36,37] .…”
Section: Pet Imaging Of Presynaptic Dopaminergic Functionsmentioning
confidence: 89%
“…This pattern has been reported not only in sporadic PD but also in juvenile, young-onset parkinsonism and patients with parkin gene mutations. Whereas the latter notions were derived mainly from PET investigations, similar observations would have been obtained by the use of DAT SPECT ligands (19)(20)(21).…”
Section: Proof Of Neurodegenerative Psmentioning
confidence: 92%